The Relationship Of Perception With Blood Donation Interest In Pmi, Serdang Bedagai District, 2021 - Syahferi Anwar (Science Midwifery, 2022)
There are still many people who think that donated blood is traded by the Indonesian Red Cross and has a negative opinion on the implementation of blood donors because when people need blood, they still have to be charged a bag fee taken at the blood donation unit. This study aims to determine the relationship between perceptions with interest in blood donation at PMI Serdang Bedagai Regency in 2021. The method used in this study was cross sectional to see the relationship between perceptions and interest in blood donors at PMI Serdang Bedagai in 2021. The sample in this study amounted to 135 people. The type of research used is quantitative research with a descriptive approach. The research instrument used was a questionnaire using a Likert scale. The results of this study indicate that the perception of blood donors is categorized as moderate with a percentage of 72.6% while the majority of donor interest is weak with a percentage of 64.4% with p-value = 0.003 < = 0.05 which means that there is a significant relationship between the perception variable and interest in blood donors. at PMI Serdang Bedagai Regency in 2021 by using chi-square analysis. It can be concluded that there is a significant and strong relationship between the variables of perception of blood donors and interest in blood donors, because it is the perception of blood donors that is influencing blood donor interest.